RANCANG BANGUN APLIKASI JASA CUCI SEPATU BERBASIS ANDROID DENGAN LOCATION BASED SERVICE DI SMOOTHLY SHOESCARE - Evodi, Gabriel Jevon; Mardhiyyah, Rodhiyah (Program Studi Informatika Universitas Teknologi Sumbawa, 2024)
Smoothly Shoescare is a shoe cleaning and maintenance service provider in Yogyakarta facing challenges in managing transaction data and service delivery. The data collection process is currently conducted manually, from filling out order forms via WhatsApp or customers visiting in person, to recording transaction data in physical books. This manual method leads to negative impacts such as redundancy, damage, and loss of customer and transaction data. Additionally, the ordering process through WhatsApp is time-consuming due to slow and accumulating chat confirmations. In the shoe pickup and delivery process, there is a problem with insufficient accessibility to customer addresses, causing delivery delays due to inaccurate location points. The application being developed is mobile-based for customers and web-based for service providers. In designing the application, the Unified Modelling Language (UML) method is used to visually represent the system design. The mobile application is built using the Flutter framework, while the system used by service providers employs the Next.js framework. The result of this research is an online-accessible shoe cleaning service application with features capable of addressing the issues faced by Smoothly Shoescare. This application can accurately determine pickup and delivery location points by utilizing Location Based Service technology.